Brand Equity as an Economic Asset in Shaping Consumer Loyalty and Purchase Intentions for Erigo Products - Rabbani, Muhammad Zikry; Cahyani, Putri Dwi; Ningrum, Nonik Kusuma (International Journal of Economics Development Research (IJEDR), 2025)
This study examines the influence of Brand Awareness, Brand Image, and Brand Equity on Consumers’ Purchase Intention in the context of Erigo products. Conducted in Yogyakarta, the research involved a sample of 126 Erigo product users who had made at least one purchase. Respondents were selected based on a minimum age criterion of 17 years and prior purchasing experience with Erigo. Data were processed using SPSS to analyze the relationships between the studied variables. The findings indicate that Brand Awareness, Brand Image, and Brand Equity each have a significant positive impact on Consumers’ Purchase Intention, demonstrating the crucial role of branding in influencing consumer purchasing decisions.